Kierunki doskonalenia systemu zarządzania środowiskowego - Brzozowski, Tomasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The implementation of environmental management system (EMS) is the first step to the continuous improvement of corporate environmental activities. On this ground organizations improve their structures, processes and products by the implementation of new technology, materials and the reduction of resources consumption. The environmental performance of an organization is of increasing importance to internal and external interested parties. It can essentially influence their market rating. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (7); 2007; nr 1185, s. 41-47